Pogue's war : diaries of a WWII combat historian - Pogue, Forrest C. (Book collections on Project MUSE., 2001)
"With a foreword by Stephen Ambrose and a preface by Franklin D. Anderson Forrest Pogue (1912-1996) was undoubtedly one of the greatest World War II combat historians. Born and educated in Kentucky, he is perhaps best known for his definitive four-volume biography of General George C. Marshall. But, as Pogue's War makes clear, he was also a pioneer in the development of oral history in the twentieth century, as well as an impressive interviewer with an ability to relate to people at all levels, from the private in the trenches to the general carrying four stars. Pogue's War is drawn from Forr